Case Report: Primary NK/T Cell Lymphoma Nasal Type of the Colon With Multiple Intestinal Perforations - Zhang, Yan; Liu, Weiping; Zhang, Xinyue; Wu, Bing (Frontiers in Oncology, 2021)
Background: Extranodal NK/T cell lymphoma is a rare non-Hodgkin lymphoma mainly involving the upper aerodigestive tract, even rarer is primary extranasal disease involving the intestine. We present a case of primary intestinal NK/T cell lymphoma with diagnostic challenge, which eventually developed into multiple intestinal perforations. Case presentation: A 35-year-old man presented with diarrhea and recurrent fever. Abdominal CT revealed multi-segmental intestinal wall thickening. Colonoscopy showed multiple irregular ulcers in colon. During the hospitalization, the patient developed intestinal perforation and an emergency surgery was performed. The resected specimen showed multiple perforations of the colon. The surgical samples underwent pathological analysis, and a diagnosis of extranodal NK/T cell lymphoma nasal type was confirmed. After recovering from surgery, the patient started receiving chemotherapy. Fortunately, he was discharged after significant improvement in his general condition. Conclusion: Early diagnosis of primary intestinal NK/T cell lymphoma is frequently difficult. Most patients were definitely diagnosed only after surgical resection following complications, resulting in a poor prognosis. Therefore doctors should maintain high suspicion of this malignancy for early diagnosis at an early stage clinically.